Intelligent decision support System for precision medicine (IDSS 4 PM) - Mosavi, Nasimsadat (2021)
Availability of healthcare big data and limited human cognitive to decide timely, from one hand and unsuccessful business model of traditional Medical Decision Making(MDM), on the other hand, have challenged the healthcare/medicine landscape to pioneer Precision Medicine (PM). This study aims to propose the conceptual framework of the Intelligent Decision Support system for Precision Medicine (IDSS4 PM), by highlighting the fundamental role of key technologies.